Towards Faster and More Inclusive Growth An Approach to the 11th Five Year Plan - Planning Commission (Planning Commission Government of India, 2006)
The 11th Five-Year Plan (2007–2012) of India outlines a strategic framework to achieve faster and more inclusive economic growth, targeting a GDP growth of 9–10% while addressing disparities across regions and social groups. The plan emphasizes strengthening agricultural productivity, creating employment opportunities, and expanding access to quality education, healthcare, and social services, particularly for marginalized populations including Scheduled Castes, Scheduled Tribes, women, and rural communities. Key initiatives include promotion of Micro, Small, and Medium Enterprises (MSMEs), development of rural and urban infrastructure through Public-Private Partnerships, environmental sustainability, and enhanced governance via decentralization and civil society engagement. Educational reforms focus on universal elementary education, adult literacy, and merit-based higher education access, while health initiatives prioritize maternal and child care, mental health, and gender-sensitive interventions. By integrating investment, institutional reforms, and inclusive policies, the plan aims to transform economic growth into equitable social development, ensuring that the benefits of progress reach all sections of society.
Government of India Planning Commission Yojana Bhawan New Delhi December 2006
Keywords: Inclusive Growth; 11th Five-Year Plan; Rural Development; Agriculture Productivity; Employment Generation; Social Infrastructure; Micro Small Medium Enterprises; Education Reform; Health Initiatives; Gender Equity; Environmental Sustainability